Manajemen Pembelajaran Digital Melalui Pendekatan Plan, Do, Check, Act Cycle pada Program Studi Pendidikan Agama Kristen - Berdinata Massang; Hotliong Verawaty; Gerialdo Nuryadi (Institut Agama Kristen Negeri Manado, 2021)
ABSTRACT.This study aims to explain the use of the PDCA approach in digital-based learning management in the Christian Religious Education Study Program, Faculty of Christian Education, IAKN Manado. The type of research used in this research is qualitative research. The researcher acts as a key instrument, with data collection techniques including participant observation and interviews, data analysis techniques using the Miles and Huberman model, through power reduction, data presentation, and drawing conclusions. The results showed that: (1) learning planning is carried out by making lesson plans, choosing digital learning media that is adjusted to the material and characteristics of learning, (2) the implementation of digital learning is carried out according to the plan, if there are problems, the lecturers make appropriate changes to overcome the problems, supported by competent lecturers always improve competence by participating in various seminars and trainings, as well as support from the institution in training remote training programs, (3) learning checks are carried out by paying attention to student attendance and assignments, monitoring and evaluation of learning will be carried out by the end of the semester by LPM, (4) in this cycle it is a continuation of the planning, implementation, and inspection cycle. If it is in accordance with the expected goals, then it is continued to improve the quality of learning, if not, it will be continued with changes or modifications of parameters and components in learning. Evaluate and adjust with appropriate methods and media to solve existing problems.